2012
DOI: 10.1089/hgtb.2011.199
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Effective Method to Generate Lentiviral Vectors forEx VivoGene Delivery to Mature Human Peripheral Blood Lymphocytes

Abstract: Human ex vivo gene therapy protocols have been used successfully to treat a variety of genetic disorders, infectious diseases, and cancer. Murine oncoretroviruses (specifically, gammaretroviruses) have served as the primary gene delivery vehicles for these trials. However, in some cases, such vectors have been associated with insertional mutagenesis. As a result, alternative vector platforms such as lentiviral vectors (LVVs) are being developed. LVVs may provide advantages compared with gammaretroviral vectors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…To minimize the effects of this contamination, we treated viral supernatants with the endonuclease Benzonase to degrade residual plasmid DNA. This method is well established in preparation of clinical-grade lentivirus for gene therapy applications ( Sastry et al 2004 ; Yang et al 2012 ; Segura et al 2013 ); however, to our knowledge, it has not been previously reported to be used in preparation of lentivirus for genetic screens or other tissue culture applications. We demonstrate that Benzonase treatment can significantly increase the fidelity of specific detection of integrated viral genomes from the genomic DNA of a population of infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…To minimize the effects of this contamination, we treated viral supernatants with the endonuclease Benzonase to degrade residual plasmid DNA. This method is well established in preparation of clinical-grade lentivirus for gene therapy applications ( Sastry et al 2004 ; Yang et al 2012 ; Segura et al 2013 ); however, to our knowledge, it has not been previously reported to be used in preparation of lentivirus for genetic screens or other tissue culture applications. We demonstrate that Benzonase treatment can significantly increase the fidelity of specific detection of integrated viral genomes from the genomic DNA of a population of infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of the gene therapy product often depends heavily on the transduction efficiency of the viral vector and the selected MOI. The lentiviral vector is the most common viral vector used to produce CAR-CD19 T cells [ 18 ]. Because of their capacity to stably integrate into the host cell genome and infect both dividing and non-dividing cells, these vectors have been extensively used for gene and cellular therapy [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…vector used to produce CAR-CD19 T cells [18]. Because of their capacity to stably integrate into the host cell genome and infect both dividing and non-dividing cells, these vectors have been extensively used for gene and cellular therapy [19,20].…”
Section: Plos Onementioning
confidence: 99%
“…The genetic modification of peripheral blood lymphocytes using retroviral vectors encoding T cell receptors (TCR) or chimeric antigen receptors (CAR) that effectively redirect T cells to recognize and eliminate tumor cells has been developed and can potentially overcome major technical obstacles, including the low frequency of natural tumor-specific T cells residing within the patient's T cell repertoire ( Johnson et al, 2009;Gilham et al, 2012;Uttenthal et al, 2012). Indeed, protocols to generate gene-modified T cells for clinical application have been developed (Lamers et al, 2002;Yang et al, 2008Yang et al, , 2010Yang et al, , 2012b. To date, retroviral vectors have been the primary choice for gene delivery into primary human T cells.…”
Section: Introductionmentioning
confidence: 99%